PHYSICAL EDUCATION AND SPORTS THEORY, ITS APPLIED ASPECTS - Abbasov Bakhadir Asatillaevich (Web of Journals Publishing, 2025)
Sport permeates all levels of modern society, exerting a wide impact on the main spheres of society. It influences national relations, business life, social status, shapes fashion, ethical values, and people's way of life. Every profession has its own functions and techniques, as well as definitions and concepts specific to a particular profession.
Keywords: Physical education, sport theory, port specialists, achievement, professional technique, competence.